Corporate Income Tax Rates Reduction and Earnings Management: Empirical Evidence from Indonesia - Suwardi, Eko; Saragih, Arfah Habib; Fajri, R Muhammad (The Indonesian Journal of Accounting Research, 2024)
In response to the reduction of Indonesia's corporate income tax rate (from 25% to 22%), this paper investigates whether companies engage in earnings management. This study employed a mean difference test to analyze a sample of companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. The findings of this study show that companies implemented earnings management practices in 2018, 2020, and 2021 in response to the implementation of a reduction in corporate income tax rates. However, there is no indication of earnings management practices in 2019 and 2022. Further findings from the mean difference test show that, in general, companies are increasingly adopting income decreases from the two periods before (2018 and 2019) to the two periods after (2020 and 2021) the drops in tax rates. Finally, additional analysis reveals disparities in earnings management strategies between profitable and loss-making companies. Company management can manage its profits in response to changes in tax regulations by reducing corporate income tax rates. By doing so, companies can gain a certain amount of tax savings. Overall, the findings of this study are expected to be interesting and important for policymakers